2005
DOI: 10.1177/014107680509801012
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Drugs in Popular Movies: An Analysis of the top 200 Films

Abstract: We analyse the portrayal of sex and drug use in the most popular movies of the last 20 years using the Internet Movie Database list of the top 200 movies of all time. Films released or set prior to the HIV era (pre 1983), animated, not about humans or G/PG rated, were excluded. Films were reviewed by one of two teams of two observers using a data extraction sheet tested for inter-rater reliability. Sexual activity, sexually transmitted disease (STD) prevention, birth control measures, drug use and any conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
0
10
0
3
Order By: Relevance
“…Scripts provide behavioral options in social situations, including those that may lead to sexual behavior, and the content of scripts is often influenced by media. As mentioned in the previous section, movies generally offer permissive and risky sexual messages to viewers (Gunasekera et al, 2005; Nalkur et al, 2010), and a higher degree of sexual media exposure has been found to predict more permissive sexual attitudes (Bleakley, Hennessy, Fishbein, Coles, & Jordan, 2009; Brown, Halpern, & L’Engle, 2005). Furthermore, adolescents sometimes seek out sexual media, possibly to learn these scripts (Brown et al, 2005).…”
Section: How Media Influence Sexual Behaviormentioning
confidence: 85%
See 1 more Smart Citation
“…Scripts provide behavioral options in social situations, including those that may lead to sexual behavior, and the content of scripts is often influenced by media. As mentioned in the previous section, movies generally offer permissive and risky sexual messages to viewers (Gunasekera et al, 2005; Nalkur et al, 2010), and a higher degree of sexual media exposure has been found to predict more permissive sexual attitudes (Bleakley, Hennessy, Fishbein, Coles, & Jordan, 2009; Brown, Halpern, & L’Engle, 2005). Furthermore, adolescents sometimes seek out sexual media, possibly to learn these scripts (Brown et al, 2005).…”
Section: How Media Influence Sexual Behaviormentioning
confidence: 85%
“…Potentially even more important for adolescents’ sexual health, however, is that most of these movies do not portray safe sex. A content analysis revealed that 70% of the sexual acts depicted in movies released from 1983 to 2003 occurred between newly acquainted partners, 98% included no reference to contraception, and 89% resulted in no consequences (Gunasekera, Chapman, & Campbell, 2005). Additionally, Pardun, L’Engle, and Brown (2005) found that only 9% of sexual content in movies contained messages promoting sexual health.…”
Section: Sex In the Moviesmentioning
confidence: 99%
“…Selon les études sur les représentations des drogues illicites dans les médias de divertissement, notamment au cinéma, entre 15 % et un tiers des films y faisaient référence (Roberts, Henriksen et Christenson, 1999 ;Gunasekera, Chapman et Campbell, 2005 ;Terre et al, 2006 ;Callister et al, 2012), alors que la proportion des séries télévisuelles présentant ces substances atteignait 20 % (McCaffrey et al, 2000 ).…”
Section: Représentations Des Drogues Et Autres Substances Dans Les Téunclassified
“…Quant aux médicaments, 29 % des films y faisaient référence, mais l'étude ne précise pas si leur consommation obéissait à des objectifs médicaux ou à des recherches de sensations. Une autre étude portant sur deux cents films populaires dans différents pays, produits entre 1983 et 2003 (Gunasekera, Chapman et Campbell, 2005), indique que 15 % d'entre eux contenaient des références à des drogues illicites (8 % au cannabis, 7 % à d'autres substances). Les personnages qui avaient recours au cannabis étaient généralement des adultes et ce type de consommation était le plus souvent représenté de façon positive et sans conséquence probléma-tique.…”
Section: Représentations Des Drogues Et Autres Substances Dans Les Téunclassified
See 1 more Smart Citation